Story Box : Animal Adventures - Boldt, Claudia, ....- (London : Laurence King Publishing Ltd, 2019)
Make your own exciting stories by joining all 20 double-sided puzzle pieces, mixing and interchanging the pieces to allow for different endings, plots en twists.
Bevat 20 dubbelzijdig bedrukte puzzelstukken.
Keywords: Dierenverhalen